Performance Test of Biogas Production from Tapioca Wastewater: Effect of HRT and Immobilized Media - Sanjaya, Andri; Arhab, jabir Shoji; Salsabila, Dwinda; Damayanti, Damayanti; Fahni, Yunita; Deviany, Deviany; Agustryani, Putri; Auriyani, Wika Atro; Saputri, Desi Riana (Eksergi, 2026)
Tapioca starch industry wastewater contains high concentrations of organic matter, offering potential for renewable energy generation via biogas production. This study evaluates the effects of hydraulic retention time (HRT) variation and Lampung natural zeolite as an immobilization medium on biogas production in an anaerobic reactor. Two reactor configurations were compared: one with zeolite as the microbial immobilization medium and a control reactor without any immobilization media. Zeolite improved the sCOD degradation efficiency up to 93% compared to the non-immobilized reactor. VFA conversion to methane remained more stable with zeolite, producing up to 520 mL of biogas at a 10-day HRT, with an average biogas yield of 61.97 mL/g dry substrate, much higher than 4.15 mL/g in the non-immobilized reactor. This research confirms the effectiveness of Lampung natural zeolite for enhancing microbial retention, accelerating methanogenesis, and improving overall anaerobic reactor performance. These results have substantial implications for developing efficient, sustainable, and environmentally friendly treatment technologies for tapioca starch wastewater, offering simultaneous solutions for pollution control and renewable energy generation.